Resource depletion, pollen coupling, and the ecology of mast seeding. (30th May 2014) - Crone, Elizabeth E.; Rapp, Joshua M.
Abstract : Masting, the highly variable and synchronous production of seeds across a population of perennial plants, is an ecologically important, but still poorly understood, phenomenon. While much is known about the fitness benefits of masting and its effects on seed consumers and trophic interactions, less is understood about the proximate mechanisms of masting. The resource budget model (RBM) posits that masting requires more resources than plants can gain in a single year. Individual plants store resources until a threshold is reached and then produce seeds, which depletes resources so that plants cannot reproduce again for 2 or more years. Individuals are synchronized by pollen coupling or environmental forcing. We review the assumptions of these models and assess the extent to which they are consistent with general patterns in plant populations. We discuss the implications of the RBM for how plants respond to changes in the external environment. Overall, the RBM is a likely cause of synchrony in many, but not all, masting species. This mechanistic hypothesis also leads to specific, but not always intuitive, expectations about how plant resources affect mast seeding.